Oliver's story [videorecording (DVD)] - Korty, John; O'Neal, Ryan; Bergen, Candice, 1946-; Milland, Ray; Segal, Erich, 1937-2010 (Paramount DVD, 2003)
In this sequel to Love Story, widower Oliver tries to rebuild his life and finds himself falling in love again.